Islamic and conventional behavioral finance: A critical review of literature - Musse, Osman Sayid Hassan; Echchabi, Abdelghani; Abd. Aziz, Hassanuddeen (King Abdulaziz University Scientific Publishing Center, 2015)
The purpose of this study is to critically analyze existing literature on behavioral finance and to draw conclusions and recommendations for future studies in this area. The study is based on a critical review of the literature of Islamic and conventional behavioral finance. The findings reveal that investors are affected by psychological and social factors toward their financial decision-making process with respect to investment and choosing a particular financial product. The paper concludes that Islamic behavioral finance is a relatively new and efforts are needed to advance work in this area compared with the more advanced conventional behavioral finance. Behavioral issues are, however, gaining considerable attention from a broad spectrum of investors, especially those in the Muslim world.